Pengaruh penerapan material flow cost accounting terhadap green accounting dan financial performance - Rahmania Santi, Afra; Andi, Kiagus; Lindrianasari, Lindrianasari; Oktavia, Reni (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study is to test and determine the application of Material Flow Cost Accounting in improving green accounting. Furthermore, this study aims to examine whether Material Flow Cost Accounting has an impact on a company's profitability. The research topic used in this study is the basic materials and chemical industry companies listed on the Indonesian Stock Exchange (IDX) during the period 2018-2020. The data used are from the company's annual report. Features descriptive statistical tests, linear regression, and R-squared tests. The results show that the application of Material Flow Cost Accounting (MFCA) has a significant impact on green accounting, while the research results related to the application of Material Flow Cost Accounting (MFCA) has a significant impact on improving financial performance. Return on Assets (ROA) proxy for industrial companies. Basic materials and chemicals listed on the Indonesian Stock Exchange. Because Material Flow Cost Accounting helps provide information on the flow of raw materials, energy, and factories, it is easier to identify material waste, facilitate optimal allocation of environmental funds, and increase operational awareness. Managers are aware of the costs associated with wasted materials and can identify opportunities to increase the efficiency of material usage and improve the company's financial performance.